2008
DOI: 10.1088/0022-3727/41/3/035503
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of embedded lateral stress gauge profiles in shocked targets

Abstract: In principle, stress gauges mounted to measure lateral stresses in a shocked matrix allow the shear strength of the material to be determined. However, interpreting the resistance profiles from lateral stress gauges is hindered by the fact that the stress field in the vicinity of the insulating layer in which the gauges are embedded can differ significantly from the stress field that would be generated in the sample if no gauge were present. A series of high resolution Eulerian hydrocode simulations have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 16 publications
5
28
0
Order By: Relevance
“…Firstly, the gradient behind the shock appears constant and independent of the nature of gauge encapsulation. This is consistent with the work by Appleby-Thomas et al [5], and suggests that matrix/encapsulation dispersion [7][8][9] has no influence on the measured lateral stress at the gauge. Further, the magnitude of the gradients in Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Firstly, the gradient behind the shock appears constant and independent of the nature of gauge encapsulation. This is consistent with the work by Appleby-Thomas et al [5], and suggests that matrix/encapsulation dispersion [7][8][9] has no influence on the measured lateral stress at the gauge. Further, the magnitude of the gradients in Fig.…”
Section: Resultssupporting
confidence: 91%
“…Secondly, it is notable that an overshoot in stress on shock arrival occurs for the two dry-joint targets; whereas no such feature is apparent for the glued-joint arrangements. Combined with the negative gradient behind the shock, such behaviour would be consistent with the phenomenon of Mach stem formation (attributable to a lower interlayer shock velocity) proposed by Winter and Harris [7,8] and Winter et al [9]. However, if this were the case, the lack of a shock in the air filled layer should result in a significantly steeper gradient in the dry-joint case.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…However, this is an inherently invasive approach, complicating interpretation. Recent computational modelling by Winter and Harris [8,9] and Winter et al [10] has highlighted on-going debate within the shock physics community [2][3][4][5][6][8][9][10][11]. In these works, the complexity of the embedded gauge environment was studied and a potential link between perceived changes in strength behind the shock and shock dispersion between the encapsulation and target material was demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, recent extensions of the models discussed in Refs. [8][9][10] have suggested that this equilibration time may also be influenced by extrusion of the central encapsulation material under high-rate loading. To this end, here, the effect of variation of the geometric environment of embedded gauges on their response in tantalum (Ta), which is known to show variation in lateral stress behaviour behindthe-shock [12], was experimentally interrogated.…”
Section: Introductionmentioning
confidence: 99%